DEVELOPMENT OF MATHEMATICAL DIGITAL COMICS WITH ETHNOMATEMATICS APPROACH TO CLASS III ELEMENTARY SCHOOL ON WEIGHT UNIT CONVERSION MATERIAL - Sabilla Putri Arliani; Siti Khabibah (MATHEdunesa, 2022)
Technological developments have affected most aspects of human life, including education. The role of technology in education can be found in the development of learning media. One of the difficulties faced by students is connecting the mathematics they get in school with real life. Digital comics with an ethnomathematical approach can be one of the potential learning media to connect school mathematics with the real world. The purpose of this research is to develop and produce a mathematical digital comic with an ethnomathematical approach for converting weight units from g to kg and vice versa for grade III SD which is suitable for use. The method used is ADDIE. The criteria for evaluating digital comics used are valid, practical, and effective. The selection of research subjects was carried out using a purposive sampling technique and the subjects obtained were 20 third grade elementary school students and two media expert validators as well as material experts. The results showed that the digital comics developed met the valid criteria with a validity level of 80.35%, practical with a practicality percentage of 81.87%, and effective because 100% of students passed the KKM. So it can be concluded that the digital comics developed are suitable for use in mathematics learning activities because they meet the criteria of validity, practicality, and effectiveness and are expected to be used by educators as learning media to increase enthusiasm and improve student learning outcomes.